Tourism Inflows and Renewable Electricity Transition in Southeast and East Asian Economies: Within-Country Evidence, 2000–2019 - Husni Muhamad Rifqi; Yahya Fikri; Ahmed Taha Elmekawy (Global Review of Tourism and Social Sciences, 2026)
Tourism growth is often assumed to accelerate renewable-energy adoption, yet observed relationships may reflect persistent differences among countries rather than changes within them. This study tests whether international tourist arrivals predict the renewable share of electricity generation in a balanced panel of Cambodia, China, Lao PDR, Malaysia, Myanmar, the Philippines, and Singapore from 2000 to 2019 (N = 140). Pooled correlations are compared with two-way country and year fixed-effects regressions controlling for GDP per capita and population. The pooled association is negative (r = −0.562), largely reflecting contrasts between hydropower-rich, lower-tourism economies and tourism-intensive economies with limited domestic renewable generation. After fixed effects are introduced, tourism coefficients are statistically insignificant across linear, extended, and non-linear specifications. The results indicate that annual tourism growth does not systematically alter national electricity composition; renewable transition appears more closely tied to structural endowment, energy policy, and investment conditions